2017
DOI: 10.1002/cctc.201701379
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Biocatalytic Reductive Aminations by Extending the Imine Reductase Toolbox

Abstract: Chiral secondary and tertiary amines are ubiquitous in pharmaceutical, fine, and specialty chemicals, but their synthesis typically suffers from significant sustainability and selectivity challenges. Biocatalytic alternatives, such as enzyme‐catalyzed reductive amination, offer several advantages over traditional chemistry, but industrial applicability has not yet been demonstrated. Herein, we report the use of cell lysates expressing imine reductases operating at 1:1 stoichiometry for a variety of amines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
91
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 33 publications
0
91
0
3
Order By: Relevance
“…[14,15] When presented with ketones, such as acetophenone, and a large excess of ammonia or other amine, these NADPH-dependent enzymes catalyze the asymmetric reduction of imines formed in solution, to give chiral amine products such as α-methylbenzylamine (3 b) in a theoretically quantitative yield and with high enantiomeric excess (Scheme 2). A subgroup of IRED enzymes, reductive aminases (RedAms) [16][17][18] has also been shown to catalyze the formation of the iminium ion with certain ketone and amine partners, with the consequence that the coupling [a] D.…”
mentioning
confidence: 99%
“…[14,15] When presented with ketones, such as acetophenone, and a large excess of ammonia or other amine, these NADPH-dependent enzymes catalyze the asymmetric reduction of imines formed in solution, to give chiral amine products such as α-methylbenzylamine (3 b) in a theoretically quantitative yield and with high enantiomeric excess (Scheme 2). A subgroup of IRED enzymes, reductive aminases (RedAms) [16][17][18] has also been shown to catalyze the formation of the iminium ion with certain ketone and amine partners, with the consequence that the coupling [a] D.…”
mentioning
confidence: 99%
“…These included 44 new enzymes and 4 previously disclosed ones (Table S1 and Figure S1 in the Support-ing Information). [10][11] Genes encoding these IREDs were synthesized based on the codon bias of E. coli, cloned into pET28a or pET21a, and overexpressed in E. coli BL21 (DE3). The resulting cell-free extracts were used to examine their activity and enantioselectivity towards substrate 4 h, and the results are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…One of the more recent additions to the suite of biocatalysts available for chiral amine synthesis are imine reductases (IREDs), which catalyze the asymmetric reduction of prochiral imines by using the cofactor NADPH (Figure a) . It has also been shown that, as well as the reduction of preformed imines, certain enzymes of this class can also enable reductive amination between a carbonyl and amine substrate . Furthermore, we recently identified enzymes from a subgroup of the IRED enzyme family that catalyze imine formation as well as imine reduction.…”
Section: Figurementioning
confidence: 99%
“…Aniline ( d ), was also a substrate for several of the biocatalysts. Due to the lower nucleophilicity of arylamine systems compared to simple alkylamines, enzymes that are capable of utilizing d in reductive aminations with ketones are of particular interest, with some recent advances in this area made independently by Roiban et al . during the course of our investigations.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation